On Roman religion: lived religion and the individual in ancient Rome - Rüpke, Jörg (Townsend lectures/Cornell studies in classical philology, 2016)
Individual appropriation of religion -- Individual decision and differences of social order in late republican Roman priesthoods -- Appropriating images embodying gods -- Testing the limits of ritual choices -- Reconstructing religious experience -- Dynamics of individual appropriation -- Religious communication -- Instructing literary practice in the Shepherd of Hermas